The role of generics and biosimilars in the availability of medicines – challenges of similarity - Tubić, Biljana (Archives of Pharmacy, 2022)
Generic is a medicine essentially similar to an already approved original medicine (originator). Biosimilar is a biological medicine that is similar to an already approved original biological medicine (originator biologic). As opposed to originator, extensive non-clinical and clinical studies are not required for licensing generics and biosimilars. Due to smaller financial investments, the prices of generics and biosimilars are lower than the prices of the originators. The limitations for replacing the originators with the generics are existing only for the pharmaceuticals with a narrow therapeutic range and with variable interindividual absorption. The limitations of replacing the originator biologic with biosimilars are more extensive. One of the main reasons for this is a lack of experience with biosimilars and a lack of trust in the safety of biosimilars. Biological medicines are made by living organisms. A minor change in manufacturing of biologics may lead to differences in the structure, stability, and occur a serious immune reaction or lack of efficacy. The assessment of similarity between originator biologic and biosimilar must be based on the extensive product characterization and an abridged non-clinical and clinical data. Norway is the first country that has “opened the doors” for biosimilars. Their experience to date has shown that the biosimilars are safe and efficacious as originators. It is necessary to raise the level of knowledge about biological therapy and to develop policy documents with clear instructions for the switching and substitution of medicines. Pharmacists should take the main role in this process.